2018
DOI: 10.1177/1024907918808156
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations and causes of gelsemium poisoning in Hong Kong from 2005 to 2017: Review of 33 cases

Abstract: Background: Gelsemium elegans is an extremely toxic plant, but gelsemium poisoning is seldom reported in the English literature. Objectives: To evaluate the clinical manifestations and causes of gelsemium poisoning in Hong Kong. Methods: A retrospective review of gelsemium poisoning recorded by the Hong Kong Poison Information Centre from 2005 to 2017. Results: In total, 33 cases (55% female, median age 44 (interquartile range: 30–56)) were identified in 14 incidences. Consumption of contaminated Ficus hirta (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It can dispel wind and blood stasis, reduce swelling, relieve pain, and kill insects. In recent years, pharmacological studies have shown that Gelsemium elegans has many functions, including analgesic effects, sedation, anti-inflammation, mydriatic effects, antitumor, reduced heart rate, heart contraction inhibition, increasing blood pressure, and improving immunity [6,7]. The antitumor effect of Gelsemium elegans provides an attractive prospect for research and development.…”
Section: Introductionmentioning
confidence: 99%
“…It can dispel wind and blood stasis, reduce swelling, relieve pain, and kill insects. In recent years, pharmacological studies have shown that Gelsemium elegans has many functions, including analgesic effects, sedation, anti-inflammation, mydriatic effects, antitumor, reduced heart rate, heart contraction inhibition, increasing blood pressure, and improving immunity [6,7]. The antitumor effect of Gelsemium elegans provides an attractive prospect for research and development.…”
Section: Introductionmentioning
confidence: 99%